Research Contributions of CCS Haryana Agricultural University, Hisar : A Bibliometric Analysis - Siwach, Anil Kumar; Parmar, Seema (DESIDOC Journal of Library & Information Technology, 2018)
CCS Haryana Agricultural University (CCSHAU) is among the top ten agricultural universities of India according to ICAR ranking 2016-17. The present study has been undertaken to find out the publication trends in this university during 2001-2015. The study mainly focus on year-wise research output, major subject categories, national and international collaborations, top journals for publications, most prolific authors, citations pattern and highly cited papers of CCSHAU. The results indicate that among the top ten agricultural universities of India, CCSHAU stands at fourth position in terms of publications and sixth position in terms of citations. It has collaborated with many institutions at national and international level in its research publications.